Uji Kandungan Antioksidan dan Flavonoid Pada Ekstrak Daun Tanaman Mahoni (Swietenia mahagoni) - Mita Julia; Dyah Ayu Sri Hartanti; Siti Aminatuz Zuhria (Universitas PGRI Adi Buana Surabaya, 2022)
Mahagony plants are found in Indonesia. The leaves of this plant contain high levels of antioxidants and flavonoids, so they can be useful as antioxidant. In the study, mahogany leaves were extracted using the maceration extraction method, after obtaining the mahogany leaf extract, further tests were carried out to determine the antioxidant and flavonoid content in it. Antioxidant testing was carried out using the DPPH method (1.1 Dhipenyl 2 Pycnihydrazy). namely 2500 ppm, 1250 ppm, 625 ppm, 3125 ppm and also 156.25 ppm. The ability of antioxidant compounds contained in each concentration was 2500 ppm at 76 09%, 1250 ppm at 70.57%, 625 ppm at 67 96% 3125 ppm absatat 61 77% and 1565 at 13.95% The lowest inhibitory power was found at the highest concentration. ie 2500 ppm Mahogany leaves are strong antioxidants, as evidenced by a high value of 1650 (IC50 100) in the results of the mahogany plant leaf extract test. While the content of flavonoids shows that in the leaves of the mahogany plant there is a flavonoid actxawa. Total levels of flavonoids dissolved in a concentration of 100 ppm achesar 44.4 QEg This study is able to provide information about the potential of mahagony plant leaves as antioxidants.